2023
DOI: 10.1093/jas/skad189
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of developmental-stage-dependent piRNAs in Tibetan sheep testes

Abstract: The core function of the testes is to produce sperms, which is the prerequisite for maintaining male fertility. PIWI-interacting RNAs (piRNAs) are a class of non-coding small RNAs that are mainly enriched in the reproductive organ and play a key role in germ cell development and spermatogenesis. However, the expression and function of piRNAs in the testes of Tibetan sheep, a domestic animal endemic to the Tibetan Plateau, remain unknown. In this study, we evaluated the sequence structure, expression profile, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Long intergenic ncRNA (lincRNA) deletions also reduced fertility in male C. elegans nematodes [71]. Interestingly, other studies showed that age-related differentially expressed piRNAs in spermatozoa are mainly involved in gene expression, transcription, protein modification, and cell development during spermatogenesis and testicular development [63,72].…”
Section: Non-coding Rna and Senescent Spermatozoamentioning
confidence: 99%
“…Long intergenic ncRNA (lincRNA) deletions also reduced fertility in male C. elegans nematodes [71]. Interestingly, other studies showed that age-related differentially expressed piRNAs in spermatozoa are mainly involved in gene expression, transcription, protein modification, and cell development during spermatogenesis and testicular development [63,72].…”
Section: Non-coding Rna and Senescent Spermatozoamentioning
confidence: 99%
“…Therefore, studying histomorphologic changes in the testis and the developmental pattern of spermatogenic cells is essential for controlling the reproductive process and regulating the fertility of animals. To date, study of testicular and spermatogenic epithelial cell development to control the developmental and reproductive stages of animals has been widely undertaken in mice, cats, pigs, sheep, and other animals [9][10][11][12]. In our research, we applied a similar approach to the genus Equus.…”
Section: Introductionmentioning
confidence: 99%